Production Of Word Stress In Children - 3-4 years - Raju Pratap (Journal of All India Institute of Speech and Hearing, 1970)
Learning the phonology of a language involves not only segmental aspects, but supra segmental aspects as well. Supra segmental features includeintonation, rhythm, and stress. Stress refers to the increased effort and effort is one of the parameters of fluency. It would be important to consider theparameter effort when one wants to understand fluency and its disorders. In this context, the present study was planned. It aims at studying the developmentof word stress in the age range of three to four years old normal children who were native Kannada speakers.